Normative Motivation in Whistleblowing Decision Making - Doe, Raymond; Landrum, Bryan A.; Barclay, Eli J.; Carona, Ken M. (Journal of Organizational Psychology, 2020)
Whistleblowing presents a conundrum – either the decision is heralded as the ultimate justice or it is perceived as the ultimate betrayal. The opportunity cost of fairness or loyalty occurs within a personal, situational, or cultural contexts. When would an employee decide to report an unethical behavior? This study adopts the theory of planned behavior to manipulate these normative beliefs in addition to the motivations and then measure the intention of whistleblowing in an organizational context. Using a sample of 162 participants, the results showed a significant interaction between the normative beliefs and the motivations as well as a main effect of normative beliefs on the intention of whistleblowing.